The (unobservable) value of central bank's refinancing operations - Ugo Albertazzi; Lorenzo Burlon; Tomas Jankauskas; Nicola Pavanini (European Central Bank (ECB), 2020)
We quantify the impact that central bank refinancing o perations a nd f unding f acilities had at reducing the banking sector's intrinsic fragility in the euro area in 2014-2019. We do so by constructing, estimating and calibrating a micro-structural model of imperfect competition in the banking sector that allows for runs in the form of multiple equilibria, in the spirit of Diamond & Dybvig (1983), banks' default and contagion, and central bank funding. Our framework incorporates demand and supply for insured and uninsured deposits, and for loans to firms and households, as well as borrowers' default. The estimation and the calibration are based on confidential granular data for the euro area banking sector, including information on the amount of deposits covered by the deposit guarantee scheme and the borrowing from the European Central Bank (ECB). We document that the quantitative relevance of non-fundamental risk is potentially large in the euro area banking sector, as witnessed by the presence of alternative equilibria with run-type features, but also that central bank interventions exerted a crucial role in containing fundamental as well as non-fundamental risk. Our counterfactuals show that 1 percentage point reduction (increase) in the ECB lending rate of its refinancing operations reduces (increases) the median of banks' default risk across equilibria by around 50%, with substantial heterogeneity of this pass-through across time, banks and countries.
Keywords: E44; E52; E58; G01; G21; L13; 330; Central bank policies; Bank runs; Multiple equilibria; Imperfect competition; Structural estimation